2020
DOI: 10.1038/s41467-020-15655-5
|View full text |Cite
|
Sign up to set email alerts
|

A double-hit of stress and low-grade inflammation on functional brain network mediates posttraumatic stress symptoms

Abstract: Growing evidence indicates a reciprocal relationship between low-grade systemic inflammation and stress exposure towards increased vulnerability to neuropsychiatric disorders, including posttraumatic stress disorder (PTSD). However, the neural correlates of this reciprocity and their influence on the subsequent development of PTSD are largely unknown. Here we investigated alterations in functional connectivity among brain networks related to low-grade inflammation and stress exposure using two large independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…A growing body of evidence indicates a significant association between peripheral proinflammatory markers such as plasma IL1β in stress and trauma-related disorders [ 39 , 41 , 115 , 116 ]. PBMCs isolated from subjects with PTSD also exhibit significantly higher spontaneous production of IL1β and other proinflammatory cytokines, which correlate well with the severity of the PTSD symptoms [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence indicates a significant association between peripheral proinflammatory markers such as plasma IL1β in stress and trauma-related disorders [ 39 , 41 , 115 , 116 ]. PBMCs isolated from subjects with PTSD also exhibit significantly higher spontaneous production of IL1β and other proinflammatory cytokines, which correlate well with the severity of the PTSD symptoms [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of transcripts with overlapping expression profile between blood and brain in stress disorders suggests the importance of peripheral inflammation in stress disorders [ 115 , 117 ]. Recent studies have shown that increased peripheral inflammation can predict altered functional connectivity in the major brain regions related to anxiety in the depression and PTSD [ 116 , 118 ]. Through there is a wide consensus that a few of the inflammatory markers, especially IL1β, are enhanced in blood following stress, however, bi-directional relationship, i.e., if peripheral inflammation contributes to stress disorders is not well understood [ 11 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, el estrés crónico origina una respuesta inflamatoria sostenida perjudicial. La inflamación, por tanto, actúa como elemento beneficioso y perjudicial para el organismo, ya que es un componente esencial de la inmunovigilancia y la defensa del huésped, mientras que un estado inflamatorio crónico de bajo grado, entendido como la presencia crónica de factores proinflamatorios que pueden surgir de factores estresantes persistentes en el cuerpo, incluido un mayor estrés oxidativo y psicosocial, es característico de una amplia gama de enfermedades crónicas como el síndrome metabólico, la esteatosis hepática no alcohólica, la diabetes mellitus tipo 2 o la arterioesclerosis 9 , así como de enfermedades neuropsiquiátricas y neurocognitivas, incluidos los trastornos neurodegenerativos, la depresión, la psicosis, el autismo, el abuso de sustancias, en especial, el alcohol, los trastornos del sueño y la epilepsia 4 , 5 .…”
Section: Afectación Del Sistema Nervioso Centralunclassified
“…In line with the immunometabolic hypothesis, studies have shown that genetic polymorphisms in inflammatory genes such as interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNFα) and C-reactive protein, influence depression incidence, severity, and treatment response ( Barnes et al, 2017 ; de Kluiver et al, 2019 , 2021 ; Draganov et al, 2019 ; Kappelmann et al, 2021 ). Meanwhile, psychosocial stress, the main environmental risk factor for depression, was linked to changes in adenosine triphosphate (ATP) mediated P2X7 receptor (P2X7R) signaling and related to neuroinflammation ( Kendler et al, 1999 ; Iwata et al, 2013 ; Rohleder, 2014 ; Calcia et al, 2016 ; Nelson et al, 2017 ; Maydych, 2019 ; Ribeiro et al, 2019 ; Kim et al, 2020 ). Therefore, innate, and adaptive immunity involving P2X7R is currently deemed a key player in stress-induced depression ( Wohleb et al, 2016 ; Leday et al, 2018 ; Giollabhui et al, 2020 ; Illes et al, 2020 ; Troubat et al, 2020 ; von Muecke-Heim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%